What do nursing students need in learning English? - Ami Pradana; Wisma Yunita; Irma Diani (UNIB Press, 2022)
This study aimed at investigating the needs of English-specific purposes materials for nursing students at the Dehasen University of Bengkulu. It focused on the existing materials used by English lecturers, target situation (the purpose of learning English, materials needed, and topics needed), and the activities needed by nursing students from students’ and stakeholders’ perception. This research was a mixed-method that involved forty-nine nursing students and nine stakeholders. The data of this research were collected by using a questionnaire, documentation, and interview. The results of the study revealed that the existing materials used by the English teachers tended to general English materials. In addition, the analysis results of target situation show that; 1) most students learn English for looking for jobs; 2) the most needed language proficiency components were vocabulary mastery, speaking and listening skill; 3) the materials needed in each language skill and knowledge were the materials that were related to nursing activities and job; 4) almost all of the topics were needed by nursing students such as giving information on treatment plans or diagnosis. Moreover, the learning activities needed by nursing students were in terms of the workgroup (small group, large group, and pairs) and discussion. In conclusion, the findings describe that student need the real English learning materials in nursing profession and the appropriate learning activities that can make them interact and work together with their classmates.